Polyphenols from wolfberry and their bioactivities. (1st January 2017) - Zhou, Zheng-Qun; Xiao, Jia; Fan, Hong-Xia; Yu, Yang; He, Rong-Rong; Feng, Xiao-Lin; Kurihara, Hiroshi; So, Kwok-Fai; Yao, Xin-Sheng; Gao, Hao
Highlights: This research represented a systematic work on wolfberry polyphenols. 53 major polyphenols including 9 new phenylpropanoids and a new coumarin were identified. 22 known polyphenols were the first isolates from the genus Lycium . Antioxidant and anti-Alzheimer's disease activities of all polyphenols were evaluated. Structure–antioxidant activity relationship of phenylpropanoids was proposed. Abstract: Nine new phenylpropanoids, one new coumarin, and 43 known polyphenols were isolated from wolfberry. Their structures were determined by spectroscopic analyses, chemical methods, and comparison of NMR data. Polyphenols, an important type of natural products, are notable constituents in wolfberry. 53 polyphenols, including 28 phenylpropanoids, four coumarins, eight lignans, five flavonoids, three isoflavonoids, two chlorogenic acid derivatives, and three other constituents, were identified from wolfberry. Lignans and isoflavonoids were firstly reported from wolfberry. 22 known polyphenols were the first isolates from the genus Lycium . This research presents a systematic study on wolfberry polyphenols, including their bioactivities. All these compounds exhibited oxygen radical absorbance capacity (ORAC), and some compounds displayed DPPH radical scavenging activity. One compound had acetylcholinesterase inhibitory activity. The discovery of new polyphenols and their bioactivities is beneficial for understanding the scientific basis of the effects of wolfberry.